Tingkat pengetahuan penanggulangan bencana dan kesiapsiagaan bencana gempa bumi pada kepala keluarga di Dusun Kiringan Canden Jetis Bantul Yogyakarta - Niken Setyaningrum; Rizal Rumagutawan (Health Sciences and Pharmacy Journal, 2018)
Head of Family knowledge about earthquake disaster management is very important in disaster preparedness, it is expected that the community is ready to handle earthquake disaster. In order not to panic and grow negatively against them. The people of Kiringan village are very affected by the earthquake disaster due to disaster prone areas. The purpose of this research is to know the relationship of knowledge level of disaster management with earthquake disaster preparedness to family head in Kiringan Village, Canden, Jetis, Bantul, Yogyakarta. There search used quantitative research type with analytic observation with crosssectional design. The sampling technique using consecutive sampling and samples in this study were 57 family heads in Kiringan Village Canden Jetis Bantul Yogyakarta. Bivariate analysis using spearman rank test. There wasn’t significant correlation between knowledge level of disaster management with earthquake disaster preparedness in the head of family in Kiringan village, Canden, Jetis, Village, Bantul, Yogyakarta got value of Correlation Coefficient 0.104, with significant value equal to 0.441 (p value 0.05). There was nocorrelation between knowledge level of disaster management with earthquake disaster preparedness on family head in Kiringan Village, Canden, Jetis, Bantul, Yogyakarta.